PRIMARY EMPTY SELLA SYNDROME PRESENTING WITH SEVERE HYPONATREMIA AND MINIMAL SALT WASTING - Aijazi, Ishma; Al Shama, Fadil Mustafa Abdullah; Mukhtar, Sara Hussein Adam (Journal of Ayub Medical College Abbottabad, 2016)
A 41 year old Jordanian gentleman known case of osteogenesis imperfecta presented with vomiting, decreased oral intake followed by confusion. At presentation he was found to have signs of hypogonadism with severe hyponatremia. The hyponatremia responded to intravenous steroid replacement .This alerted the physicians to search for other pituitary hormone deficiencies. Our patient had pneumonia with respiratory failure. He was intubated and mechanically ventilated. Subsequent tracheostomy was done because of failure of weaning. His GCS remained very low despite treatment of infection and correction of electrolyte imbalance. He had multiple hormone deficiencies. He was found to be severely hypothyroid, replacement of thyroxine caused gradual improvement of GCS over a period of six to eight weeks. In the absence of history pituitary adenoma, pituitary, irradiation or surgery, a diagnosis of primary empty Sella syndrome with anterior pituitary dysfunction was made. Keywords: Empty sella; hyponatremia; central hypothyroidism